The Study Of Vertical Cephalic Index (Length-Height Index) And Transverse Cephalic Index (Breadth-Height Index) Of Andhra Region (India). - Salve, Vishal Manoharrao; Chandrashekhar, Chikatapu (Asian Journal of Medical Sciences, 2013)
Background & objectives: Cephalometry is a branch of anthropometry that describes measurements of head and face in cadaveric, living or radiologic specimen. The vertical cephalic index is the ratio of the maximum height of head to its maximum length. The transverse cephalic index is the ratio of the maximum height of head to its maximum breadth. Materials and Methods: The present study was carried out with 320 (160 male & 160 female) medical students of Dr. Pinnamaneni Siddhartha Institute of Medical Sciences & Research Foundation and Dr. Sudha & Nageswara Rao Institute of Dental Sciences Chinnaoutpally, Krishna District (AP), India. Results: The mean vertical cephalic index for male was 74.08 ± 3.24 and for female was 73.03 ± 4.64. The mean transverse cephalic index for male was 97.91 ± 3.77 and for female was 93.41 ± 5.57. The differences between male and female mean vertical cephalic index and mean transverse cephalic index were significant. Discussion & conclusion: The result of present study shows that all male and female of Andhra region are hypsicephalic according to classification based on vertical cephalic index and acrocephalic according to classification based on transverse cephalic index. Vertical cephalic index of the male is 1-2 point higher than the female in Andhra region population. This data can be useful for forensic medicine experts, plastic surgeons, neurosurgeons, neurologists, anatomist, anthropologist, fasciomaxillary surgeons, oral surgeons and for clinical and research purpose. This study will serve as basis for comparison of future studies on Andhra region population of India and also South Asian population. Asian Journal of Medical Science, Volume-3 No-3 (2012), Page 6-11 DOI: http://dx.doi.org/10.3126/ajms.v3i3.4650